(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine how the legal protection of the famous brand name "IWAN TIRTA" on the trademark PT. Pusaka Iwan Tirta and Batik Iwan Tirta. As well as knowing how the provisions regarding brand impersonation analysis conducted by parties in good faith to imitate famous brand names in decision number 1299 k / pdt.sus-hki / 2017, on December 22, 2017. Based on the results of the analysis in this study, that Legal protection for famous brands is regulated in Act Number 15 of 2001 concerning Trademarks and Act Number 20 of 2016 concerning Trademarks and Geographical Indications. Regarding the case of PT PUSAKA IWAN TIRTA, it can be concluded that having bad faith has a similarity in principle with the trademark BATIK IWAN TIRTA, besides it also does not have a permit or license to use the element of the name of a famous person "IWAN TIRTA" from the owner of exclusive rights to the trademark registered BATIK IWAN TIRTA. The implementation of legal protection for well-known brands in Indonesia is in accordance with applicable law and elements of fame and bad faith can be proven in accordance with laws and regulations. It’s just that in the appeal appeal cassation decision it is necessary to add Article 41 paragraph (1) and Article 41 paragraph (2) of Law Number 20 Year 2016 Regarding Trademark and Geographical Indications in weighing and giving said decision.